The New Covenant Rhetoric in Ezekiel 11:14–21 and 36:16–38 - Pikor, Wojciech (The Biblical Annals, 2025)
In the book of Ezekiel, the new covenant is announced in 11:14–21 and 36:16–38. Crucial to these prophecies is the future renewal of the heart and spirit of Israel. While the two prophecies share numerous similarities at the level of form and content, there are also fundamental disparities between them. These are not only due to differences concerning the inner renewal but also to the rhetorical dynamic of the new covenant. To describe this dynamic, we first examine the place of the announcement of inner renewal in these prophecies. Then we analyse the rhetorical structure of Ezek 11:17–20 and 36:24–28. Finally, on the basis of these analyses, we ask the question to what extent Daniel I. Block’s thesis of resumptive exposition in the book of Ezekiel can be applied to establish the rhetorical relationship between the prophecies in question. Rhetorical analysis allows us to conclude that they are part of a work-in-progress logic. Accordingly, various affirmations of the new covenant, announced in different historical contexts, are preserved in the book. Considering other Ezekiel prophecies on the new covenant, especially those on the covenant of peace in 34:25–30 and 37:26–28, one can speak not so much of a single covenant theology as of multiple covenant theologies in the book of Ezekiel.